Silica glass, high frequency device using silica glass, and method for manufacturing silica glass

By controlling the number and diameter of bubbles in silica glass through flame hydrolysis and pressure reduction, the method addresses the limitation of existing silica glass manufacturing, achieving desired dielectric constants for high-frequency devices, reducing transmission loss and signal deterioration.

JP7601085B2Active Publication Date: 2024-12-17AGC INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022503353
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-28
Filing Date
2021-02-19
Publication Date
2024-12-17
Estimated Expiration
2041-02-19

AI Technical Summary

Technical Problem

Existing methods for manufacturing silica glass are limited in controlling density, making it difficult to achieve a dielectric constant suitable for high-frequency devices, particularly in microwaves and millimeter waves, due to the inability to produce silica glass with densities lower than 2.0 g/cm³.

Method used

A method involving flame hydrolysis of silicon compounds to form silica glass, followed by steps of depositing fine particles, heating and firing in an inert gas atmosphere, and reducing pressure to control the number and diameter of bubbles, resulting in silica glass with a density range of 0.5 to 1.95 g/cm³, which can be used as a dielectric substrate.

Benefits of technology

This approach allows for the production of silica glass with controlled dielectric constants between 1.3 and 3.5, reducing transmission loss and signal deterioration in high-frequency devices by uniformly dispersing air bubbles, thereby optimizing the dielectric properties for high-frequency applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601085000004
    Figure 0007601085000004
  • Figure 0007601085000005
    Figure 0007601085000005
  • Figure 0007601085000006
    Figure 0007601085000006
Patent Text Reader

Abstract

The present invention pertains to silica glass having a bubble number of 1×107 to 1×1015 / cm3, and having a density of 0.5-1.95 g / cm3. The present invention also pertains to a silica glass production method including: a step for obtaining a silica glass porous body by depositing SiO2 fine particles having been generated by flame-hydrolyzing a silicon compound; a step for obtaining a silica glass dense body by heating and sintering the silica glass porous body in an inert gas atmosphere; and a step for performing foam treatment by heating the silica glass dense body under a reduced pressure condition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to silica glass, a high-frequency device using silica glass, and a method for producing silica glass. [Background technology]

[0002] Conventionally, passive electronic devices in high frequency bands such as microwaves and millimeter waves include high frequency devices such as antennas, filters, duplexers, diplegers, capacitors, inductors, etc. These high frequency devices generally include a dielectric substrate such as a resin substrate, a ceramic substrate, or a glass substrate.

[0003] Recently, in order to increase communication capacity and speed, signal frequencies are becoming higher. It is known that in high-frequency devices, the higher the signal frequency, the greater the transmission loss in the dielectric substrate, causing signal degradation. In order to suppress this, it is desirable to reduce the relative dielectric constant or dielectric loss tangent of the dielectric substrate.

[0004] On the other hand, it is known that the smaller the relative dielectric constant, the larger the dielectric substrate must be, and therefore it is desirable for the dielectric substrate to have a small dielectric tangent and a dielectric constant that can be reduced according to the purpose.

[0005] The antenna device of Patent Document 1 includes a dielectric substrate, which preferably has a low dielectric tangent, and silica glass is cited as a material for the dielectric substrate.

[0006] It is known that the density and the dielectric constant of silica glass are approximately proportional to each other. When the density decreases, the dielectric constant decreases. One method for controlling the density of silica glass is to use bubbles in the glass. For example, the manufacturing method described in Patent Document 2 is generally called the VAD (Vapor-phase Axial Deposition) method, and includes a step of depositing silica glass particles (soot) to obtain a porous silica glass body, and a step of heating and firing the porous silica glass body. By optimally combining conditions such as pressure, temperature, and processing time during heating and firing, it is possible to control the diameter and number of bubbles remaining after firing, and thus the density of the obtained silica glass. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 2017-228846 [Patent Document 2] International Publication No. 2008 / 069194 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the manufacturing method described in Patent Document 2 has a limited range of controllable density. 3 Or 2.16g / cm 3 Only silica glass with a density of 2.0 g / cm 3 It is difficult to obtain silica glass having a smaller density, and therefore it has not been possible to obtain silica glass having a desired relative dielectric constant. One aspect of the present invention provides a technique for obtaining silica glass having a desired density. [Means for solving the problem]

[0009] The silica glass according to one embodiment of the present invention has a bubble count of 1×10 7 ~1×10 15pieces / cm 3 and the density is 0.5 to 1.95 g / cm 3 It is characterized in that: A method for producing silica glass according to one embodiment of the present invention includes the steps of obtaining a porous silica glass body by depositing SiO2 fine particles produced by flame hydrolysis of a silicon compound, heating and sintering the porous silica glass body in an inert gas atmosphere to obtain a dense silica glass body, and heating the dense silica glass body under reduced pressure conditions to perform a foaming treatment. Effect of the Invention

[0010] According to the present invention, by controlling the number and diameter of bubbles contained in silica glass, and thereby controlling the density, it is possible to obtain silica glass having a desired relative dielectric constant. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a cross-sectional view showing silica glass according to one embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing a part of a porous silica glass body formed during the production of silica glass according to one embodiment. [Diagram 3] FIG. 3 is a cross-sectional view showing a dense silica glass body formed during production of silica glass according to one embodiment. [Figure 4] FIG. 4 is an optical microscope image of the silica glass of Example 1. [Diagram 5] FIG. 5 is an optical microscope image of the silica glass of Example 4. [Figure 6] FIG. 6 is a diagram showing the relationship between the number of bubbles contained in the silica glass according to Examples 1 to 10 and the average major axis of the openings. [Figure 7] FIG. 7 is a graph showing the relationship between the dehydration treatment time during the production of silica glass according to Examples 1 to 12 and the OH group concentration of the obtained silica glass. [Figure 8] FIG. 8 is a graph showing the frequency dependence of the dielectric constant of the silica glasses according to Examples 1, 3, 11 and 13. [Figure 9] FIG. 9 is a diagram showing the relationship between density and relative dielectric constant of the silica glass according to Examples 1 to 13. [Figure 10] FIG. 10 is a graph showing the frequency dependence of the dielectric tangent of the silica glasses according to Examples 1, 3, 11 and 13. [Figure 11] FIG. 11 is a graph showing the relationship between the OH group concentration and the dielectric loss tangent of the silica glasses according to Examples 1 to 12. As shown in FIG. [Figure 12] FIG. 12 is a diagram showing the relationship between the average major axis and the root-mean-square height of the openings of the silica glass according to Examples 1 to 10. As shown in FIG. [Figure 13] FIG. 13 is a graph showing the mass percent concentration of gas contained in the bubbles of the silica glass of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. In the specification, the symbol "to" indicating a range of values ​​means that the values ​​before and after the symbol "to" are included as the lower and upper limits. The lower and upper limits include the range of the values ​​rounded off.

[0013] As shown in FIG. 1, silica glass 1 according to an embodiment of the present invention includes a silica glass portion 11, bubbles 12 uniformly dispersed in the silica glass portion 11, and a recess 14 having an opening 13 on the surface of the silica glass 1. The lower limit of the density of silica glass 1 is 0.5 g / cm 3 , preferably 0.7 g / cm 3 , more preferably 1.0 g / cm 3 The density is 0.5g / cm 3 By setting the density to 1.95 g / cm or more, the strength of the silica glass 1 can be sufficiently obtained. On the other hand, the upper limit of the density is 1.95 g / cm 3 , preferably 1.8 g / cm 3 , more preferably 1.65 g / cm 3 , and more preferably 1.6 g / cm 3 The density is 1.95g / cm 3By being equal to or less than this, the relative dielectric constant is not too high, making the material suitable as a dielectric substrate for use in high frequency devices. The silica glass portion 11 is transparent and has a density of about 2.2 g / cm 3 It is.

[0014] The lower limit of the number of bubbles 12 (hereinafter also referred to as the bubble count) is 1×10 7 pieces / cm 3 , preferably 3 x 10 7 pieces / cm 3 On the other hand, the upper limit of the number of bubbles is 1×10 15 pieces / cm 3 , preferably 1 x 10 14 pieces / cm 3 , and more preferably 1×10 13 pieces / cm 3 The preferred range of the number of bubbles 12 is related to the size of the opening 13 described later, but the number of bubbles is 1×10 7 pieces / cm 3 If the number of bubbles is more than 1×10, the density of the silica glass 1 does not become too high and this is an appropriate range, even if the diameter of the opening 13 is not increased. For example, when processing the silica glass 1 for use in a high-frequency device and forming a metal wiring layer on the surface of the obtained substrate, if the diameter of the opening 13 is larger than the wiring width, the substrate wiring layer cannot be formed as designed, which may cause device malfunction. 7 pieces / cm 3 If the number of bubbles is 1×10 or more, there is no risk of contamination. 15 pieces / cm 3 If it is less than this, there is no risk that the bubbles will be too small to disappear. At least 90 mass % of the gas contained in the bubbles 12 is He, Ne, Ar, Kr, Xe, N2, or a mixture of these gases.

[0015] The opening 13 is substantially elliptical. The diameter of the opening 13 is related to the number of bubbles. When the diameter of the opening 13 is large, the number of bubbles cannot be increased, but when the diameter of the opening 13 is small, the number of bubbles can be increased. As mentioned above, if the diameter of the opening 13 is too large, it is disadvantageous for forming, for example, a metal wiring layer. In recent years, the wiring width of a metal wiring layer for high-frequency devices has been reduced, and it is considered desirable that the width is at least preferably 30 μm or less, more preferably 10 μm or less, even more preferably 5 μm or less, and particularly preferably 1 μm or less. Therefore, it is required that the average value of the major axis of the opening is preferably 30 μm or less, more preferably 10 μm or less, even more preferably 5 μm or less, and particularly preferably 1 μm or less.

[0016] The silica glass 1 preferably has an OH group content of 100 ppm or less, more preferably 50 ppm or less. The smaller the OH group content, the smaller the dielectric tangent (Reference: JP-A-7-330357). In the specification, ppm means parts per million, and ppb means parts per billion.

[0017] The silica glass 1 contains each of the metal impurities Li, Na, Mg, Al, K, Ca, Cr, Mn, Fe, Ni, Cu, Ti, Co, and Zn at 0.5 mass ppm or less. The smaller the content of metal impurities, the more the occurrence of metal contamination can be suppressed in the process of processing the silica glass 1 for use in high-frequency devices, and the higher the yield.

[0018] The silica glass 1 has a relative dielectric constant in the frequency range of 20 GHz to 110 GHz of preferably 1.3 to 3.5, and more preferably 1.5 to 3.5. If the relative dielectric constant is within this range, when the silica glass 1 is used in a filter for a high-frequency device, for example, the device can be made sufficiently small while ensuring a wide operating bandwidth.

[0019] The silica glass 1 having the above-mentioned relative dielectric constant can be suitably used as a member for use in a plasma etching apparatus for semiconductor manufacturing. For example, when used as a member for use in a plasma processing chamber, the low relative dielectric constant reduces electrical distortion, so that the generation of unnecessary plasma can be minimized. In this case, the temperature during use is assumed to be 50 to 200°C, the pressure is assumed to be 150 Pa or less, and the relative dielectric constant is preferably 1.3 to 3.5 in the frequency range of 100 kHz to 200 MHz.

[0020] The silica glass 1 preferably has a dielectric loss tangent of 1.0×10 in the frequency range of 20 GHz to 110 GHz. -5 ~5.0×10 -4 If the dielectric loss tangent is sufficiently small in this way, when the silica glass 1 is used as a dielectric substrate for a high-frequency device, for example, it is possible to suppress signal degradation due to transmission loss.

[0021] The optically polished silica glass 1 preferably has a root mean square height of the glass surface of 1 μm or less. If the root mean square height is sufficiently small, for example, when a conductor layer is formed on the surface of the optically polished silica glass 1 for use in a high-frequency device, an increase in transmission loss caused by skin current can be suppressed. In order to further suppress transmission loss, the surface of the optically polished silica glass 1 may be smoothed by a method such as fire polishing or CO2 laser. In the present specification, optical polishing refers to polishing performed using a slurry containing an abrasive. As the abrasive, cerium oxide particles, silicon oxide particles, aluminum oxide particles, zirconium oxide particles, titanium oxide particles, diamond particles, silicon carbide particles, etc. are used.

[0022] Next, a method for producing silica glass according to an embodiment of the present invention will be described. In the present invention, the VAD method is used as a method for synthesizing silica glass, but the production method may be appropriately changed as long as the effects of the present invention are achieved.

[0023] (1) Selection of synthetic raw materials The raw material for synthesizing silica glass is not particularly limited as long as it is a gasifiable raw material, but representative examples include silicon chlorides such as SiCl4, SiHCl3, SiH2Cl2, and SiCH3Cl3, silicon halide compounds such as fluorides such as SiF4, SiHF3, and SiH2F2, and RnSi(OR) 4-n (wherein R is an alkyl group having 1 to 4 carbon atoms, and n is an integer of 0 to 3) and halogen-free silicon compounds such as (CH3)3Si-O-Si(CH3)3 are examples.

[0024] (2) Formation of porous silica glass The above synthesis raw material is subjected to flame hydrolysis preferably at a temperature of 1000 to 1500°C to synthesize SiO2 fine particles, which are then deposited on a rotating substrate to form a porous silica glass body 2 as shown in Figure 2. The porous silica glass body 2 is a porous body formed by fusing primary particles 21 of SiO2 fine particles, and has many pores 22 that communicate with the outside.

[0025] (3) Dehydration It is preferable to perform a dehydration treatment by heating the silica glass porous body 2 at a high temperature in a vacuum atmosphere. Although the dehydration treatment is not essential, it is preferable to perform the dehydration treatment because, as described later, this step reduces the OH group concentration of the silica glass 1 obtained later and reduces the dielectric tangent. The heating temperature during the dehydration treatment is preferably 1000 to 1300° C. If the temperature is 1000° C. or higher, the dehydration reaction proceeds sufficiently, and if the temperature is 1300° C. or lower, there is no risk of the densification of the porous body proceeding faster than the progress of the dehydration reaction. The dehydration treatment time may be within 240 hours at the above heating temperature. The longer the treatment time, the lower the OH group concentration becomes, but if the treatment time is too long, the production efficiency decreases.

[0026] (4) Heating and baking When the dehydrated porous silica glass body 2 is pressurized in an inert gas atmosphere and heated and fired at a high temperature, a dense silica glass body is obtained in which the pores 22 communicating with the outside are completely closed. During heating and firing, the inert gas dissolves in the silica glass. The inert gas is typically He, Ne, Ar, Kr, Xe, N2, or a mixture of these gases, with Ar being preferred, as described in detail below. It is known that the solubility of the inert gas in the silica glass tends to increase as the partial pressure of the inert gas in the atmosphere increases or the temperature of the silica glass decreases. The pressure range during firing is preferably 0.01 to 200 MPa. If the pressure is 0.01 MPa or more, the inert gas dissolves sufficiently, and if the pressure is 200 MPa or less, there is no risk of the inert gas dissolving excessively. As will be described later, the amount of dissolved inert gas affects the degree of foaming in the subsequent foaming treatment. The heating temperature during firing is preferably 1200 to 1700° C., and is preferably higher than the heating temperature during the dehydration treatment. If the heating temperature is 1200° C. or higher, firing proceeds sufficiently, and if the heating temperature is 1700° C. or lower, there is no risk of volatilization of glass components. The calcination time is preferably 10 to 100 hours, more preferably 20 to 60 hours, at the above pressure and heating temperature. If the treatment time is 10 hours or more, calcination and dissolution of the inert gas proceed sufficiently, and if it is 100 hours or less, production efficiency is good.

[0027] (5) Foaming treatment Next, the silica glass dense body is depressurized to a pressure preferably less than 0.01 MPa and heated at a high temperature, whereby the inert gas dissolved in the silica glass foams or the bubbles in the silica glass dense body thermally expand, thereby obtaining silica glass 1 having uniformly dispersed bubbles 12. The foaming mechanism will now be described. As mentioned above, it is known that the solubility of an inert gas in silica glass tends to increase as the partial pressure of the inert gas in the atmosphere increases or the temperature of the silica glass decreases. Therefore, if heating is performed under conditions of lower pressure or higher temperature than during heating and sintering in the foaming treatment, the difference between the amount of dissolved gas during heating and sintering and the amount of dissolved gas during the foaming treatment will be in a supersaturated state, and foaming of the inert gas will occur within the dense silica glass body. Among the above-mentioned types of inert gas, Ar is preferable because it is relatively inexpensive, has a large temperature dependency of solubility, and makes it easy to control the degree of foaming. The heating temperature during the foaming treatment is preferably 1300 to 1800° C., and is preferably higher than the heating temperature during the firing. If the heating temperature is 1300° C. or higher, sufficient foaming or thermal expansion can be obtained, and if it is 1800° C. or lower, there is no risk of the glass material bursting due to excessive foaming or thermal expansion. The foaming treatment time may be preferably 1 minute to 10 hours at the above pressure and heating temperature. If the treatment time is 1 minute or more, sufficient foaming or thermal expansion can be obtained, and if it is 10 hours or less, there is no risk of the glass material bursting due to excessive foaming or thermal expansion. By combining the pressure, heating temperature and processing time during the heating and firing and the foaming treatment, the degree of foaming of the inert gas that foams in a supersaturated state and the degree of thermal expansion of the bubbles can be changed, thereby controlling the number and diameter of the bubbles 12 contained in the silica glass 1, and thereby controlling the density. EXAMPLES

[0028] Next, the experimental data will be described mainly with reference to Tables 1 and 2 and FIGS. The physical properties of the silica glass 1, the transparent silica glass, and the dense silica glass body 3 according to each example were measured by the methods described below. Examples 1 to 10 are working examples, and Examples 11 to 16 are comparative examples.

[0029] (density) The density was calculated by the Archimedes method for a glass sample of about 20 g using a molecular balance manufactured by Shimadzu Corporation (product name: AP224W).

[0030] (Average long diameter of opening) The cut surface of the silica glass 1 was optically polished, and an optical microscope image (270 μm × 340 μm) of the cut surface was obtained. Then, 125 μm × 160 μm sections were extracted from the four corners of the optical microscope image, and the average value of the long diameter of the openings 13 included in the sections was calculated, and the average of the four average values ​​was taken as the average long diameter of the openings. Note that, for the openings 13 that were on the frame lines of the sections, those whose long diameters were clearly not measurable were excluded, and for the openings 13 formed by the merging of multiple openings, the long diameter was measured by inferring the shape of each opening from the outline of the openings 13 formed by the merging of multiple openings.

[0031] (Number of bubbles) The number of bubbles was calculated from the following formula (1), assuming that all of the bubbles 12 contained in the silica glass 1 have the same spherical shape and that the diameter of the sphere is equal to the average major axis of the openings.

[0032]

number

[0033] In the above formula (1), ρ is the density of silica glass 1 (unit: g / cm 3 ), d is the average major axis of the opening (unit: cm), and the unit of the number of bubbles is bubbles / cm 3 It is.

[0034] (Dielectric constant and dielectric tangent) The dielectric constant and dielectric loss tangent were measured for a glass sample of 50 mm x 40 mm x 0.3 mm using a cavity resonator and a vector network analyzer according to the method described in JIS-R1641 (2007).

[0035] (Root Mean Square Height) The root mean square height was measured by optically polishing the cut surface of a glass sample of an appropriate size and following the method described in JIS-B0601 (2013).

[0036] (Composition of gas contained in bubbles) The composition of the gas contained in the bubbles 12 was measured by crushing an appropriate glass sample in a vacuum chamber, collecting the gas in the bubbles 12, and then using a mass spectrometer.

[0037] (Metal impurity content) The content of metal impurities was measured for glass samples cut to an appropriate size by an ICP-MS (Inductively Coupled Plasma-Mass Spectrometer) method.

[0038] (OH group concentration) The OH group concentration was calculated by obtaining an IR spectrum of a glass sample having an appropriate thickness using an infrared spectrophotometer and quantifying the absorption peak due to the OH group (References: JP Williams; YS Su; WR Strzegowski; BL Butler; HL Hoover; VO Altemose, Direct determination of water in glass, Ceramic. Bulletin., Vol. 55, No. 5, pp. 524, 1976). The silica glass 1, the transparent silica glass, and the dense silica glass body 3 according to each example were produced by the method described below.

[0039] (Example 1 to Example 10) The SiO2 fine particles synthesized by flame hydrolysis of SiCl4 were deposited on a rotating substrate to obtain a silica glass porous body 2. This was placed in a heating furnace, evacuated, and then heated to 1250°C. The treatment time was appropriately adjusted so that the OH group concentration of the finally obtained silica glass 1 was the value shown in Table 1, and a dehydration treatment was performed. Then, Ar gas was filled and pressurized, and the temperature was raised to a predetermined temperature and heating and firing were performed. This was returned to atmospheric pressure and naturally cooled to room temperature. The silica glass dense body obtained at this time was opaque silica glass containing a small amount of bubbles. Then, after evacuation, the temperature was raised to a predetermined temperature and a foaming treatment was performed. This was returned to atmospheric pressure, naturally cooled to room temperature, and then taken out. The obtained silica glass 1 contained uniformly dispersed bubbles 12. The pressure, heating temperature and treatment time during the heating and firing, and the heating temperature and treatment time during the foaming treatment were combined so as to obtain the density, number of bubbles, and average major axis of the openings shown in Table 1.

[0040] (Example 11~Example 12) SiO2 fine particles synthesized by flame hydrolysis of SiCl4 were deposited on a rotating substrate to obtain a silica glass porous body 2. This was placed in a heating furnace, evacuated, and then heated to 1250°C for dehydration treatment, adjusting the treatment time appropriately so as to obtain the OH group concentration shown in Table 1. The temperature was then raised to 1350°C and held for 24 hours for heating and firing. The pressure was returned to atmospheric pressure, and the body was naturally cooled to room temperature before being removed. The obtained silica glass dense body was transparent silica glass containing almost no bubbles.

[0041] (Example 13) It is a transparent silica glass produced by the direct method.

[0042] (Example 14) SiO2 fine particles synthesized by flame hydrolysis of SiCl4 were deposited on a rotating substrate to obtain a porous silica glass body 2. This was placed in a heating furnace, evacuated, heated to 1350°C, and held for 2 hours for heating and sintering. This was returned to atmospheric pressure, naturally cooled to room temperature, and then removed. At this time, since the treatment time was insufficient, the pores 22 leading to the outside were not completely closed, and a dense silica glass body 3 having pores 31 leading to the outside, as shown in Figure 3, was obtained.

[0043] (Example 15) A dense silica glass body 3 was produced in the same manner as in Example 14, except that the temperature was raised to 1320° C. during the dehydration treatment.

[0044] (Example 16) A dense silica glass body 3 was produced in the same manner as in Example 15, except that the temperature was maintained for 5 hours after heating during the dehydration treatment.

[0045] 4 shows an optical microscope image of the cut surface of the silica glass 1 according to Example 1 that was optically polished and photographed. As a result of the measurement, the average major axis of the openings was 4.1 μm, and the number of bubbles was 3.15×10 9 pieces / cm 3 It can be seen that small-sized bubbles 12 are uniformly dispersed within the silica glass 1.

[0046] 5 shows an optical microscope image of the cut surface of the silica glass 1 according to Example 4 that was optically polished and photographed. As a result of the measurement, the average major axis of the openings was 21.1 μm, and the number of bubbles was 3.70×10 7 pieces / cm 3 It can be seen that the diameter of the bubbles 12 is larger than that of Example 1, and there is some variation in the diameter, but overall the bubbles are uniformly dispersed. The reason for the variation in diameter is thought to be that the bubbles 12 are more likely to coalesce with each other during the foaming process due to their relatively large diameter.

[0047] Fig. 6 shows the relationship between the number of bubbles contained in the silica glass 1 of Examples 1 to 10 and the average major axis of the openings. As is clear from Fig. 6, the greater the number of bubbles, the smaller the average major axis of the openings.

[0048] Fig. 7 shows the relationship between the dehydration treatment time and the OH group concentration for the silica glass 1 or transparent silica glass according to Examples 1 to 12. As is clear from Fig. 7, the OH group concentration decreases as the treatment time increases, gradually approaching 0 ppm.

[0049] Fig. 8 shows the frequency dependence of the dielectric constant of the silica glass 1 or transparent silica glass according to Examples 1, 3, 11 and 13. As is clear from Fig. 8, the dielectric constant is approximately constant in the frequency range of 20 to 110 GHz.

[0050] Fig. 9 shows the relationship between density and relative dielectric constant of the silica glass 1 and transparent silica glass according to each example in Table 1. As is clear from Fig. 9, the density and relative dielectric constant of the silica glass 1 according to examples 1 to 10 are in a roughly proportional relationship. On the other hand, the transparent silica glass according to examples 1 to 13 contains almost no air bubbles, and therefore has a density of 2.2 g / cm 3 The dielectric constant was also approximately constant. Therefore, it is understood that the method for producing silica glass 1 according to the present invention can obtain silica glass 1 having a desired dielectric constant by controlling the density.

[0051] In FIG. 9, the relative dielectric constant is shown as a representative value at a frequency of 35 GHz, but it is clear from FIG. 8 that the above-mentioned approximately proportional relationship can be obtained for any frequency in the range of 20 to 110 GHz.

[0052] FIG. 10 shows the frequency dependence of the dielectric loss tangent of the silica glass 1 or transparent silica glass according to Examples 1, 3, 11 and 13. As is clear from FIG. 10, as the frequency increases, the dielectric loss tangent also increases. Furthermore, the silica glass according to Example 13, which has a relatively high OH group concentration, has a clearly larger increase rate of the dielectric loss tangent with increasing frequency than the other examples. Therefore, reducing the OH group concentration by the dehydration treatment is also advantageous in that a low dielectric loss tangent can be maintained over a wide frequency range.

[0053] Fig. 11 shows the relationship between the OH group concentration and the dielectric loss tangent for the silica glass 1 and the transparent silica glass according to Examples 1 to 12. Fig. 11 shows that as the OH group concentration increases, the dielectric loss tangent also tends to increase. In FIG. 11, the dielectric tangent is shown as a representative value at a frequency of 35 GHz, but it is clear from FIG. 10 that the same tendency can be obtained for any frequency in the range of 20 to 110 GHz.

[0054] Fig. 12 shows the relationship between the average major axis of the openings and the root-mean-square height of the silica glass 1 according to Examples 1 to 10. Fig. 12 shows that as the major axis of the openings increases, the root-mean-square height also tends to increase. This is because the larger the average major axis of the openings, the more pronounced the unevenness of the glass surface becomes.

[0055] Fig. 13 shows the mass percent concentration of the gas contained in the bubbles of silica glass 1 according to Example 1. As shown in Fig. 13, 99.5 mass % of the gas contained in the bubbles was a mixed gas of Ar and N2.

[0056] Table 2 shows the contents of metal impurities in the silica glass 1 or transparent silica glass according to Examples 1 and 11. As is clear from Table 2, the contents of each metal impurity are on the order of ppb, and are extremely small.

[0057] The dielectric loss tangents of the silica glass dense bodies 3 according to Examples 14 to 16 at a frequency of 35 GHz were measured and found to be 1.1×10 -3 , 2.5×10 -3 , 1.9×10 -3 As is clear from a comparison with Table 1, the dielectric loss tangent of the silica glass dense body 3 was significantly larger than that of the silica glass 1. This is because the dense silica glass body 3 has pores 31 that communicate with the outside, and thus easily adsorbs water from the atmosphere, increasing the concentration of OH groups. Therefore, for example, if the dense silica glass body 3 is used as a dielectric substrate for a high-frequency device, it is expected that the signal will deteriorate due to the large transmission loss.

[0058] The silica glass, the high-frequency device using the silica glass, and the method for manufacturing the silica glass according to the present invention have been described above, but the present invention is not limited to the above-mentioned embodiments. Various changes, modifications, substitutions, additions, deletions, and combinations are possible within the scope of the claims. These naturally fall within the technical scope of the present invention.

[0059] [Table 1]

[0060] [Table 2]

[0061] Although the present invention has been described in detail and with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2020-034258) filed on February 28, 2020, the contents of which are incorporated herein by reference. [Explanation of symbols]

[0062] 1. Silica glass 11 Silica Glass Section 12 Bubbles 13 Opening 14 Recess 2. Porous silica glass 21 Primary particles of SiO2 fine particles 22 Pores leading to the outside 3. Dense silica glass 31 Pores leading to the outside

Claims

1. Number of bubbles: 1 x 10 7 ~1×10 15 pieces / cm 3 and the density is 0.5 to 1.95 g / cm 3 and the dielectric loss tangent in the frequency range of 20 GHz to 110 GHz is 1.0×10 −5 to 5.0×10 −4 .

2. The density is 0.7 to 1.8 g / cm 3 2. The silica glass of claim 1 ,

3. The air bubbles are 1×10 7 ~1×10 13 pieces / cm 3 The silica glass according to claim 1 or 2, comprising:

4. 90% by mass or more of the gas contained in the bubbles is He, Ne, Ar, Kr, Xe, N 2 The silica glass according to any one of claims 1 to 3, wherein the gas is a mixture of these gases.

5. 5. Silica glass according to claim 1, wherein the average major axis of openings formed in the glass surface is 30 μm or less.

6. 6. Silica glass according to claim 1, wherein the average major axis of openings formed in the glass surface is 10 μm or less.

7. 7. Silica glass according to claim 1, having an OH group content of 100 ppm by mass or less.

8. The silica glass according to any one of claims 1 to 7, wherein the content of each of the metal impurities Li, Na, Mg, Al, K, Ca, Cr, Mn, Fe, Ni, Cu, Ti, Co and Zn is 0.5 mass ppm or less.

9. 9. Silica glass according to claim 1, having a relative dielectric constant of 1.3 to 3.5 in a frequency range of 20 GHz to 110 GHz.

10. 9. Silica glass according to claim 1, having a relative dielectric constant of 1.5 to 3.5 in a frequency range of 20 GHz to 110 GHz.

11. 11. Silica glass according to claim 1, wherein the root mean square height of the glass surface is 1 μm or less.

12. A high-frequency device using the silica glass according to any one of claims 1 to 11.

13. SiO produced by flame hydrolysis of silicon compounds 2 A method for producing silica glass, comprising the steps of: depositing fine particles to obtain a porous silica glass body; heating the porous silica glass body at 1000 to 1300°C in a vacuum atmosphere to perform a dehydration treatment; heating and firing the dehydrated porous silica glass body in an inert gas atmosphere at a temperature higher than the heating temperature in the dehydration treatment to obtain a dense silica glass body; and heating the dense silica glass body under reduced pressure conditions to perform a foaming treatment.

Citation Information

Patent Citations

  • Production of quartz glass expanded body

    JP1998029836A

  • Opaque silica glass containing fine bubble and its production

    JP1998203839A

  • Antenna device and manufacturing method thereof

    JP2017228846A

  • Synthetic opaque quartz glass and process for production thereof

    WO2008069194A1

  • Silica glass for high-frequency devices, and high-frequency device

    WO2019093182A1